Comparison between Thermal Interface Materials Made of Nano Carbon Tube (NCT) with Gad Pad 2500 in Term of Junction Temperature by Using CFD Software, FluentTM - Mazlan Mohamed; A.M. Mustafa Al Bakri; Razak Wahab; Zulhisyam Abdul Kari @ Abdullah; Mohd Sukhairi Mat Rasat; Mohd Hazim Mohamad Amini; Mohammad Amizi Ayob (2015)
his paper presents the comparison between thermal interface materials made of nano carbon tube (NCT) with Gad Pad 2500 in term of junction temperature by using CFD Software, FluentTM. 3D model of electronic packaging is built using GAMBIT and simulated using FLUENT software. The study was made for a microprocessors arranged in line under different types of inlet velocities and package (chip) powers. The results are presented in terms of average junction temperature when chip powers have been increased from 0.5 W to 2 W. The junction temperature is been observed and it was found that the junction temperature of the electronic packaging using nano carbon has lower junction temperature compare to the Gad Pad 2500. It also found that the NCT was able to reduce the junction temperature up to 20-30% compare to others thermal interface material.